Soil quality from the organic production of Presidente Figueiredo-AM (Research, Society and Development, 2022)
The management practices used in the organic farming system are based on natural processes, such as nutrient cycling. Thus, it is important that the rural producer adopts practices of maintenance or reconstitution of soil fertility. The objective of this work was to characterize the soil of organic production of properties in km 126 of BR174, Presidente Figueiredo-AM. Soil samples were collected in nine areas in the Jardim Floresta and Nova Floresta communities to analyze the physical (texture) and chemical properties. Based on the reports of soil analysis of each area collected, it was detected that the soil texture of the properties visited is very clayey (MA), and the soil fertility condition is totally inadequate for vegetable cultivation, since the pH average is 3.6, potential acidity is high (7.15 to 31.25 cmolc dm-3), as is aluminum saturation. The levels of organic matter found were very low (average of 2.3%), as were the levels of Ca, Mg, P, K, and Na for all areas studied, resulting in an average value of base saturation V=7.7%. Possibly the low productivity of organic agriculture in the Jardim Floresta and Nova Floresta communities in Presidente Figueiredo is mainly due to the inadequate chemical conditions of the soils, with high acidity and aluminum content and low fertility and organic matter. It is extremely necessary for producers in this region to adopt agricultural practices that improve the condition of these soils, so that they can use it for agriculture.